FULFIL Trial: Once-Daily Triple Therapy for Patients with Chronic Obstructive Pulmonary Disease - Lipson, David A.; Barnacle, Helen; Birk, Ruby; Brealey, Noushin; Locantore, Nicholas; Lomas, David A.; Ludwig-Sengpiel, Andrea; Mohindra, Rajat; Tabberer, Maggie; Zhu, Chang-Qing; Pascoe, Steven J. (American journal of respiratory and critical care medicine, 2017)
Randomized data comparing triple therapy with dual inhaled corticosteroid (ICS)/long-acting β -agonist (LABA) therapy in patients with chronic obstructive pulmonary disease (COPD) are limited. We compared the effects of once-daily triple therapy on lung function and health-related quality of life with twice-daily ICS/LABA therapy in patients with COPD. The FULFIL (Lung Function and Quality of Life Assessment in Chronic Obstructive Pulmonary Disease with Closed Triple Therapy) trial was a randomized, double-blind, double-dummy study comparing 24 weeks of once-daily triple therapy (fluticasone furoate/umeclidinium/vilanterol 100 μg/62.5 μg/25 μg; ELLIPTA inhaler) with twice-daily ICS/LABA therapy (budesonide/formoterol 400 μg/12 μg; Turbuhaler). A patient subgroup remained on blinded treatment for up to 52 weeks. Co-primary endpoints were change from baseline in trough FEV and in St. George's Respiratory Questionnaire (SGRQ) total score at Week 24. In the intent-to-treat population (n = 1,810) at Week 24 for triple therapy (n = 911) and ICS/LABA therapy (n = 899), mean changes from baseline in FEV were 142 ml (95% confidence interval [CI], 126 to 158) and -29 ml (95% CI, -46 to -13), respectively, and mean changes from baseline in SGRQ scores were -6.6 units (95% CI, -7.4 to -5.7) and -4.3 units (95% CI, -5.2 to -3.4), respectively. For both endpoints, the between-group differences were statistically significant (P < 0.001). There was a statistically significant reduction in moderate/severe exacerbation rate with triple therapy versus dual ICS/LABA therapy (35% reduction; 95% CI, 14-51; P = 0.002). The safety profile of triple therapy reflected the known profiles of the components. These results support the benefits of single-inhaler triple therapy compared with ICS/LABA therapy in patients with advanced COPD. Clinical trial registered with www.clinicaltrials.gov (NCT02345161).